2015
DOI: 10.1039/c4an01682c
|View full text |Cite
|
Sign up to set email alerts
|

Significantly enhanced antibacterial activity of TiO2 nanofibers with hierarchical nanostructures and controlled crystallinity

Abstract: Recently, there has been increased interest in electrospun-titanium dioxide nanofibers (TiO2 NFs) as antibacterial agents owing to their advantages, such as simple and cost-effective fabrication processes, and high surface areas. However, the photocatalytic effects of TiO2 NFs are relatively low because of their low-ordered crystalline structure, and the antibacterial effect is only effective under UV illumination owing to their large band-gap energy. In this paper, we have demonstrated a significantly enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 38 publications
0
25
0
1
Order By: Relevance
“…That is why the zone of inhibition decreases slightly as the Al 2 O 3 content increases. In addition to alumina and silver nanoparticles, TiO 2 is another one of the most popular antibacterial additives, and it features long‐term chemical and physical stability and low‐cost preparation. To better exploitation of TiO 2 , Wang et al designed a novel air filtration membrane using electrospun poly(lactic acid)/titania (PLA/TiO 2 ), which presented excellent antibacterial activity up to 99.5%, high filtration efficiency reaching 99.996% and a relatively low pressure drop (128.7 Pa).…”
Section: Electrospun Nanofibrous Membranes For Air Filtrationmentioning
confidence: 99%
See 1 more Smart Citation
“…That is why the zone of inhibition decreases slightly as the Al 2 O 3 content increases. In addition to alumina and silver nanoparticles, TiO 2 is another one of the most popular antibacterial additives, and it features long‐term chemical and physical stability and low‐cost preparation. To better exploitation of TiO 2 , Wang et al designed a novel air filtration membrane using electrospun poly(lactic acid)/titania (PLA/TiO 2 ), which presented excellent antibacterial activity up to 99.5%, high filtration efficiency reaching 99.996% and a relatively low pressure drop (128.7 Pa).…”
Section: Electrospun Nanofibrous Membranes For Air Filtrationmentioning
confidence: 99%
“…To better exploitation of TiO 2 , Wang et al designed a novel air filtration membrane using electrospun poly(lactic acid)/titania (PLA/TiO 2 ), which presented excellent antibacterial activity up to 99.5%, high filtration efficiency reaching 99.996% and a relatively low pressure drop (128.7 Pa). The antibacterial performance of TiO 2 is further enhanced in nanoscale materials owing to a high surface‐to‐volume ratio, as the photochemical reaction mainly occurs on its surface . There are some reports that attempt to combine Ag nanoparticles with TiO 2 to further enhance their antimicrobial activity by virtue of synergistic reactions.…”
Section: Electrospun Nanofibrous Membranes For Air Filtrationmentioning
confidence: 99%
“…The highest filtration efficiency (≈100%) was observed with TiO 2 _F that also displayed the highest air pressure drop (≈183.47 Pa), due to its higher thickness and formation of particle agglomerates on the nanofibers due to TiO 2 nanoparticle size (21 nm in diameter). This performance can be explained by the large specific surface area and low-ordered crystalline structure of TiO 2 nanoparticles [58,59]. Zhang et al [60] demonstrated that TiO 2 loading on PAN nanofibers enhances particle removal efficiency due to the high surface-charge that improves the particle's electrostatic attraction.…”
Section: Comparison Of the Filtration Performancementioning
confidence: 99%
“…11 The ROS generated in this reaction lead to the decomposition of organic compounds 11 and have demonstrated antibacterial activity toward several bacterial strains including Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus. [12][13][14] Nanoparticles, primarily silica and zirconium oxide, are currently used in dental composite resins to increase the strength properties while reducing material shrinkage during curing. 15 There is a clear opportunity to replace these with functionalized nanomaterials that could impart additional benefits, such as antibacterial TiO 2 .…”
Section: Introductionmentioning
confidence: 99%